2016
DOI: 10.1038/srep38159
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of near-isogenic lines for brown planthopper resistance in rice cv. 9311

Abstract: Brown planthopper (BPH) is the most destructive pest of rice in Asia. To date 29 BPH resistance genes have been identified, but only a few genes are being used in breeding due to inefficient markers for marker-assisted selection (MAS) and little knowledge of the real effects of the genes. In this study we individually transferred 13 genes or QTLs (Bph14, QBph3, QBph4, Bph17, Bph15, Bph20, Bph24, Bph6, Bph3, Bph9, Bph10, Bph18 and Bph21) into cultivar 9311 by marker assisted backcross breeding (MABB). Through p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…Many cloned genes with disease resistance have been widely applied to the breeding and improvement of new GSR varieties (Jiang et al 2016;Hu et al 2016Hu et al , 2017. These included introduction of Pi2 (blast resistance gene) and Xa23 (bacterial blight resistance gene) into the photo-thermo-sensitive genic male sterile (PTGMS) line Guangzhan63-4S, which significantly enhanced the resistance of newly developed two-line hybrid breeding lines to bacterial blight and blast (Jiang et al 2015a QBph3,QBph4,Bph6,Bph3,Bph9,Bph10,Bph14,Bph15,Bph17,Bph18,Bph20,Bph21,and Bph24) were developed, which showed stronger brown planthopper resistance at the seedling stage (Xiao et al 2016). Recently, a novel gene, Bph38(t) on the long arm of chromosome 1, was mapped to a small genomic region of 496.2 kb explaining the phenotypic variation of 35.9% in a backcross population derived from a cross of HHZ and Khazar (Balachiranjeevi et al 2019).…”
Section: Green Genes For the Breeding Of New Gsr Varietiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Many cloned genes with disease resistance have been widely applied to the breeding and improvement of new GSR varieties (Jiang et al 2016;Hu et al 2016Hu et al , 2017. These included introduction of Pi2 (blast resistance gene) and Xa23 (bacterial blight resistance gene) into the photo-thermo-sensitive genic male sterile (PTGMS) line Guangzhan63-4S, which significantly enhanced the resistance of newly developed two-line hybrid breeding lines to bacterial blight and blast (Jiang et al 2015a QBph3,QBph4,Bph6,Bph3,Bph9,Bph10,Bph14,Bph15,Bph17,Bph18,Bph20,Bph21,and Bph24) were developed, which showed stronger brown planthopper resistance at the seedling stage (Xiao et al 2016). Recently, a novel gene, Bph38(t) on the long arm of chromosome 1, was mapped to a small genomic region of 496.2 kb explaining the phenotypic variation of 35.9% in a backcross population derived from a cross of HHZ and Khazar (Balachiranjeevi et al 2019).…”
Section: Green Genes For the Breeding Of New Gsr Varietiesmentioning
confidence: 99%
“…2). As a result, a large number of restorer lines, male sterile lines, and new pre-breeding lines with the advantages of disease/insect resistance, weed-competitive ability, high nitrogen-and phosphorususe efficiency, water-saving, drought tolerance, and high yield and quality were bred (Jiang et al 2015b(Jiang et al , 2016Xiao et al 2016;Wang et al 2016;Dimaano et al 2017). Meanwhile, these lines were screened and identified for their resistance to drought, low phosphorus, low nitrogen, weed-competitive ability, blast, bacterial blight, rice false smut, and rice planthopper, creating a batch of new germplasm with multiple green traits such as multi-resistance, high nutrient-use efficiency, water-saving, drought tolerance, and high yield and quality.…”
Section: Development Of New Pre-breeding Gsr Lines With Pyramided Grementioning
confidence: 99%
“…Some secondary metabolites, such as flavanoids, were found different in resistant and susceptible rice varieties, and can inhibit the feeding behavior of N. lugens at concentrations high enough ( Grayer et al 1994 , Stevenson et al 1996 ). N. lugens feeding on the resistant variety RHT generally ingested lower quantity of phloem sap, which indicated that the N. lugens was in nutritional deficiency states ( Ghaffar et al 2011 , Peñalver et al 2011 , Xiao et al 2016 ). Third, the endosymbionts are suggested to have evolved to complement the amino acids needs of their host, so that N. lugens can survive on a nutritionally imbalanced food source ( Chen et al 2011 , Xue et al 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…To date, MAS has been successfully utilized to breed plants with major BPH, GM, WBPH, and GRH resistance genes. A series of near-isogenic lines (NILs) with a single BPH resistance gene/QTL, including BPH3, bph4, BPH6, BPH9, BPH10, BPH14, BPH15, BPH17, BPH18, BPH20, BPH21, BPH24, BPH26, BPH32, qBPH3, and qBPH4, were developed in the background of the susceptible cultivar 9311 and IR24, respectively (Qiu et al 2010;Xiao et al 2016;. Furthermore, the NILs with a single GM (GM4, GM11), WBPH (Ovc, qOVA-1-3, qOVA-4, qOVA-5-1, and qOVA-5-2), and GRH (GRH1, GRH2, GRH4, GRH5, GRH6, and qGRH4) resistance genes were also developed (Yamasaki et al 2003;Fujita et al 2010b;Himabindu et al 2010;Divya et al 2015).…”
Section: Marker-assisted Selectionmentioning
confidence: 99%